Gastrointestinal symptoms as a predictor of deep endometriosis of the pelvic posterior compartment on magnetic resonance imaging. Issue 2 (June 2022) - Fadadu, Priyal Praful; Cope, Adela; Weng, Chia-Sui; Mara, Kristin; Khan, Zaraq; VanBuren, Wendaline; Burnett, Tatnai
Objective: To determine if gastrointestinal (GI) symptoms can predict deep endometriosis (DE) of the posterior pelvic compartment on magnetic resonance imaging (MRI). Methods: Patients with suspected endometriosis undergoing endometriosis protocol MRI at an academic center between 9/1/2015 and 7/31/2018 were identified. Presenting GI symptoms were collected via a standardized survey instrument prospectively at initial presentation. MRI and interdisciplinary conference notes were reviewed to identify posterior compartment DE (rectosigmoid, uterosacral ligaments, posterior cul de sac, and pelvic side walls). Associations between symptoms and DE were evaluated. Results: A total of 104 patients met inclusion criteria, and 89 (85.6%) presented with at least one GI symptom. Posterior compartment DE was identified on MRI in 47 patients (45.2%). The GI symptom that most strongly predicted DE was a bowel movement resulting in pain relief (OR 3.36, 95% CI 1.31–8.61, p = 0.012), with sensitivity, specificity, positive and negative predictive values 0.42, 0.82, 0.67, and 0.63, respectively. Other GI symptoms such as nausea, vomiting, rectal bleeding, change in frequency of bowel movements, and pain exacerbation by bowel movements did not significantly correlate to having DE. Of the 15 patients with no GI symptoms, 5 were found to have posterior compartment DE. Conclusion: In patients with suspected endometriosis, those who noted that bowel movements relieved their pain had more than three times the odds of having DE of the posterior compartment on MRI. Preoperative evaluation with MRI may be of value in these patients; however, lack of gastrointestinal symptoms does not exclude the possibility of posterior compartment DE.